1975
DOI: 10.1111/j.1432-1033.1975.tb02189.x
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent and Non‐equivalent Binding Sites for tRNA on Aminoacyl‐tRNA Synthetases

Abstract: Complexes between tRNAPhe (yeast), tRNAser (yeast) and tRNATy' (Escherichia coli) and their cognate aminoacyl-tRNA synthetases have been studied by sedimentation velocity runs in an analytical ultracentrifuge. The amount of complex formation was determined by the absorption and the sedimentation coefficients of the fast-moving boundary in the presence of excess tRNA or excess synthetase respectively. The same method has been applied to unspecific combinations of tRNAs and synthetases. Inactive material of tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
43
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 34 publications
9
43
1
Order By: Relevance
“…This is in contrast with the data that had been previously obtained in different experimental conditions of temperature and pH [lo]. It has been shown that changes in pH [15], temperature [16] or proteolysis [17] may alter the binding properties of synthetases. Therefore it was made sure that a non-proteolyzed form of tryptophanyl-tRNA synthetase was used throughout this study.…”
contrasting
confidence: 82%
“…This is in contrast with the data that had been previously obtained in different experimental conditions of temperature and pH [lo]. It has been shown that changes in pH [15], temperature [16] or proteolysis [17] may alter the binding properties of synthetases. Therefore it was made sure that a non-proteolyzed form of tryptophanyl-tRNA synthetase was used throughout this study.…”
contrasting
confidence: 82%
“…A number of oligomeric aaRS have previously been shown to exhibit activity of half of the sites despite containing multiple, seemingly chemically equivalent active and tRNA-binding sites (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)30). The mode of tRNA binding described herein argues that SepSecS may follow the sequential model of allosteric regulation (49).…”
Section: Discussionmentioning
confidence: 84%
“…These enzymes exhibit "half of the sites" activity that is presumably regulated by negative allostery. The TyrRS dimer binds one tRNA Tyr (15) and catalyzes formation of 1 mol of tyrosyl adenylate (16 -20), and tetrameric PheRS (15,21) and SepRS (22) employ two of their four catalytic and tRNA-binding sites at a time. Likewise, class II enzymes, bacterial LysRS-II (23,24), AspRS (25), and HisRS (26) and the archaeal and eukaryotic ProRS (27,28) behave according to the "half of the sites" model.…”
mentioning
confidence: 99%
“…The tRNA boundaries were compared in the presence and absence of ribosomes. A similar method has been used extensively with other interacting macromolecular systems such as tRNA and tRNA ligases; it has been described in detail elsewhere [20]. The method is even more simple in the system used in the present work because the sedimentation coefficients of free and bound tRNA are different by more than an order of magnitude (except with 30-S subunits).…”
mentioning
confidence: 90%